Achieving enhanced bone regeneration using monetite granules with bone anabolic drug conjugates (C3 and C6) in rat mandibular defects. Issue 6 (11th March 2020) - Sheikh, Zeeshan; Abdallah, Mohamed‐Nur; Al‐Jaf, Faik; Chen, Gang; Hamdan, Nader; Young, Robert N.; Grynpas, Marc D.; Glogauer, Michael
Abstract: Bone grafting procedures are commonly used to manage bone defects in the craniofacial region. Monetite is an excellent biomaterial option for bone grafting, however, it is limited by lack of osteoinduction. Several molecules can be incorporated within the monetite matrix to promote bone regeneration. The aim was to investigate whether incorporating bone forming drug conjugates (C3 and C6) within monetite can improve their ability to regenerate bone in bone defects. Bilateral bone defects were created in the mandible of 24 Sprague–Dawley rats and were then packed with monetite control, monetite+C3 or monetite+C6. After 2 and 4 weeks, post‐mortem samples were analyzed using microcomputed tomography, histology and back‐scattered electron microscopy to calculate the percentages of bone formation and remaining graft material. At 2 and 4 weeks, monetite with C3 and C6 demonstrated higher bone formation than monetite control, while monetite+C6 had the highest bone formation percentage at 4 weeks. There were no significant differences in the remaining graft material between the groups at 2 or 4 weeks. Incorporating these anabolic drug conjugates within the degradable matrix of monetite present a promising bone graft alternative for bone regeneration and repair in orthopedic as well as oral and maxillofacial applications.